Weaponizing language: legislating a Hindu India - Nagar, Ila (Cambridge University Press, 2025)
"Taking an interdisciplinary approach, this is the first book-length examination of how India's Hindu nationalist government uses language as a weapon against its Muslim citizens. It is essential reading for academic researchers and students in sociolinguistics, as well as South Asia studies, gender studies and Indian politics and culture"-- Provided by publisher